PENGARUH MOTIVASI KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DEWAN KOPERASI INDONESIA (DEKOPIN) - Anna Suzana (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2017)
Human Resources (HR) is a critical success factor for any organization including Indonesia Cooperative Council, to enhance its role should be supported and depends on the ability to innovate. So in order to improve performance and innovation to be able to excel and competitive in completing the work is strongly influenced by factors of motivation and organizational culture.This study aims to determine whether there is influence work motivation on employee performance, the influence of organizational culture on performance and Influence of Work Motivation and Organizational Culture on employee performance where the analysis of the data used is descriptive analysis and path analysis (path analysis).The research was conducted order to develop recommendations to improve measures to improve employee performance improvement and optimization of the work.Keywords: human resources, motivation, organizational culture, performance.